Proceedings of the Fourth ACM International Conference on Web Search and Data Mining 2011
DOI: 10.1145/1935826.1935905
|View full text |Cite
|
Sign up to set email alerts
|

A probabilistic approach for learning folksonomies from structured data

Abstract: Learning structured representations has emerged as an important problem in many domains, including document and Web data mining, bioinformatics, and image analysis. One approach to learning complex structures is to integrate many smaller, incomplete and noisy structure fragments. In this work, we present an unsupervised probabilistic approach that extends affinity propagation [7] to combine the small ontological fragments into a collection of integrated, consistent, and larger folksonomies. This is a challengi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 13 publications
(17 citation statements)
references
References 19 publications
0
17
0
Order By: Relevance
“…A very closely related problem is that given by the automatized categorization of free tags appearing in various online content (Heymann and Garcia-Molina, 2006;Schmitz, 2006;Damme et al, 2007;Plangprasopchok et al, 2011;Tibély et al, 2013;Velardi et al, 2013). In recent years, the voluntary tagging of photos, films, books and so on, with free words has become popular on the Internet in blogs, various file-sharing platforms, online stores and news portals.…”
Section: Extracting a Nested Hierarchymentioning
confidence: 99%
“…A very closely related problem is that given by the automatized categorization of free tags appearing in various online content (Heymann and Garcia-Molina, 2006;Schmitz, 2006;Damme et al, 2007;Plangprasopchok et al, 2011;Tibély et al, 2013;Velardi et al, 2013). In recent years, the voluntary tagging of photos, films, books and so on, with free words has become popular on the Internet in blogs, various file-sharing platforms, online stores and news portals.…”
Section: Extracting a Nested Hierarchymentioning
confidence: 99%
“…Plangprasopchok and Lerman (2009) introduced statistical frameworks that use user-specified relations and aggregate individual hierarchies. Later they (Plangprasopchok et al, 2011) described an unsupervised probabilistic approach that integrated smaller, noisy structures into a few complex structures. Plangprasopchok et al (2010) learned folksonomies from social metadata on Flickr by using relational clustering.…”
Section: Folksonomiesmentioning
confidence: 99%
“…Following Plangprasopchok et al [13] we call a directory a user creates to organize photos on Flickr a sapling. 1 The root node of the sapling corresponds to a user's collection, and inherits its name, while the leaves correspond to the collection's constituent sets (or other collections) and inherit their names. The photos the user assigns to a set are tagged, and we propagate these tags to sets and to their parent collections.…”
Section: A Structured Annotationsmentioning
confidence: 99%
“…We call the latter users experts and the former novice. By manually inspecting saplings created by Flickr users, we found that structure and semantic consistency are two important factors distinguishing expert from novice 1 Saplings are not always tree-like. In these cases we convert them to trees.…”
Section: A Structured Annotationsmentioning
confidence: 99%
See 1 more Smart Citation